Proposal of PAPR Reduction Method for OFDM Signal by Re-Ordering of Clusters in Frequency Domain - Tanairat Mata; Katsuhiro Naito; Pisit Boonsrimuang; Kazuo Mori; Hideo Kobayashi (My University, 2013)
One of the limitations of using OFDM technique is its higher PAPR in the time domain signal.The higher PAPR OFDM signal would cause the fatal degradation of BER performance and undesirable spectrum regrowth in the nonlinear channel.One of the promising PAPR reduction methods for OFDM signal is the Partial Transmit Sequence (PTS) method which can achieve better PAPR performance with reasonable computation complexity.However the PTS method is required to inform the phase coefficients of PTS as the side information to the receiver for the correct demodulation of data information through the data or separate channels.To simplify the transceiver of OFDM system with the PTS method, the phase coefficients of PTS are usually embedded in the data information.However since the phase coefficients of PTS are obtained after the PTS processing only for the data information at each OFDM symbol, it is hard to embed the phase coefficients of PTS in the data information separately without degradation of PAPR performance.To solve this problem, this paper proposes a new PAPR reduction method based on the packet-switched transmission systems in which all the clusters within the certain number of OFDM symbols have the sequential cluster ID numbers embedded in the header of each cluster.The salient features of the proposed method are to reduce the PAPR performance by re-ordering of clusters (ROC) in the frequency domain at the transmitter and to reconstruct the original ordering of clusters by using the cluster ID number demodulated from each cluster at the receiver.This paper also proposes a reduction technique of computation complexity for the proposed ROC method by using the feature of IFFT processing.This paper presents various computer simulation results to verify the effectiveness of the proposed ROC method with the reduction technique of computation complexity.
Keywords: Header; SIGNAL (programming language); PAPR reduction in OFDM